Arquitectura Empresarial en IPS expertos en alteraciones del desarrollo en niños (2017)
The reasons that led to this business architecture was to determine the current situation in the internal processes of IPS that serve child-adolescent population with sensory deficits, difficulties in social skills, Down syndrome, difficulties in communication and language, Autism Spectrum Disorder , Angelman syndrome, Attention Deficit Hyperactivity Disorder, between, seeking through these to favor their daily well-being and facilitate their social inclusion This business architecture will be validated at Anthiros Child Development Center, where we will look at its critical processes, and through the help of information technologies, we will support these processes, thus realizing a restructuring which contributes to the organization's objective, making them more efficient, thus improving the internal work of the institution and therefore improve the services provided.